“Fear of the Crocodile is the Beginning of Wisdom?”: Review of Dan Wylie, Crocodile - Marovich, Beatrice (Humanimalia, 2015)
Dan Wylie. Crocodile. Animal Series. London: Reaktion Books, 2013. 222 pp. £12.95; 19.95.